基于修形蜗杆砂轮的斜齿轮参数化设计 - 曾红; 刘鹏; 唐文; 王延忠 (Jixie chuandong)
According to the actual process of worm grinding wheel forming helical gear,the parameter mathematics model of the surface of helical gear and fillet is established.The helical gear tooth profile modification curve is achieved by modifying the profile of worm grinding wheel.By controlling the cutter radical feeding,the tooth profile of helical gear axial modification is achieved.By using VS 2008programming,the calculation of gear tooth surface,tooth root surface equation and the software interface design is accomplished.The feasibility of the design method is illustrated with an example.